(untitled) ("Conference on Universal Science Research 2023", 2023)
This article is about the evolution of media literacy and mass information culture and its importance in society. At the same time, its appearances are increasing. Today, the concepts of media education, media study, and media culture are used together with the concept of media literacy in receiving, sorting, analyzing, and evaluating media information.